Factores determinantes de la demanda turística en la provincia de Huánuco, región Huánuco, Perú - Calero, Roberto (2023)
Objective. Establish the factors that determine the demand for tourism resources in the province of Huánuco, Huánuco region, Peru for the year 2019. Methods. The research was of an applied type, adopting a descriptive-correlational level and a non-experimental design. A structured survey questionnaire was used to collect data from a sample of 360 households in the province of Huánuco. The units of analysis were individuals between 18 and 64 years of age who reside in the houses. Likewise, statistical associations (Spearman's rho) were estimated to determine the relationship between the variables under study. Results. They are divided into two parts: (i) through descriptive statistical analysis, it was found that the factors that determine the demand for tourism resources are: economic factors, people's tastes and preferences, and the promotion of said tourism resources; (ii) based on the inferential statistical analysis, it was found that these determining factors and tourist demand present a positive statistical association of 0.68. Conclusions. The findings indicate that if the level of income allocated to tourist activities, the tastes and preferences for visiting tourist resources, and the promotion of tourist resources in the province of Huánuco increase, the tourist demand in that area will also increase.